PELAKSANAAN WEWENANG PERAWAT UNTUK KONSULTASI DAN KOLABORASI DENGAN DOKTER DALAM PELAYANAN KESEHATAN BERDASARKAN UNDANG-UNDANG NOMOR 38 TAHUN 2014 TENTANG KEPERAWATAN (Studi di RSUD Dr. Soedirman Kebumen) - Ahmad Alfi Manala (Jurnal Idea Hukum, 2016)
The nurse’s role was caring and giving comfort to the client, which the nurse doing their position as a specific nurse, nowever, recently the nurse’s role have being expanded into  healthcare improvement and prevention of disease (prophylaxis), and also considering patient comprehensively. Nurse is demanded to have science and skill in all aspects of nursing care. Nurse as a proffesional employee, has some responsibility and authority to care and treat client independently, being able in consulting and collaborating with other health workers based on their authority, particularly related to the scope of nursing work.This research is aimed at analysis of The Implementation of the Nurse’s Authority to Consultate and Collaborate with The Doctor based on Law No. 38/2014 about Nursing which held in RSUD Dr. Soedirman Kebumen. This reseach is qualitative sociological juridical aproach, retrieval of data through observation, quisioner, the threty nurse and four informant.This research result is represented that The Implementation of the Nurse’s Authority to Consultate and Collaborate with The Doctor based on Law No. 38/2014 about Nursing section 30 of article 1 which held in RSUD Dr. Soedirman Kebumen, indicated to ‘ ineffective implementation’. This is evidenced that still many of nurses found did not do consultate and collaborate with the doctor or other health workers neither onto health service nor onto making the nursing care.Therefore, related to this infringement of law, the Nursing Concil may determine discipline of sanction to the nurse, based on Law no. 38 / 2014 section 49 and 50 about Nursing.The barrier and obstacle of the implementation of the nurse’s authority to consultate and collaborate with the doctor onto health service are: 1. The explanation of Law no. 38/2014 about what kind of expected consultation and collaboration between nurse and other health worker expecially with the doctor, is blurred. 2. Controlling and monitoring to the nurse’s ethos of work is low. 3. Level of nurse’s education is under qualify. 4. Low experience of Nurse. 5. Limited time related to rush hour of the doctor. Keyword: nurse, healty, conseling